TAXONOMY OF THE BEGONIA TILIIFOLIA GROUP, INCLUDING DESCRIPTIONS OF TWO NEW SPECIES - Tebbitt, M. C.; Hughes, M.; Pérez, Á. J.; Moonlight, P. W. (Edinburgh Journal of Botany, 2017)
Begonia albomaculata as circumscribed in the Flora of Ecuador and related publications is shown to be a misapplied name and represents an undescribed species. This is described as Begonia botryoides Moonlight & Tebbitt sp. nov., and is recorded from the Pichincha, Santo Domingo de los Tsáchilas, Napo, Cotopaxi, Azuay and El Oro provinces in Ecuador, and the Antioquia and Chocó departments of Colombia. The taxonomic study of this species prompted a re-evaluation of related species. It was subsequently found that the Central American material previously included in Begonia tiliifolia C.DC. is distinct from the type and other South American material of this species and represents an undescribed species. This is described as Begonia boreoharlingii Tebbitt & Moonlight sp. nov., and is recorded from the Limón province in Costa Rica, and the Bocas del Toro and Coclé provinces in Panama. Four species, Begonia tiliifolia C.DC., Begonia harlingii L.B.Sm. & Wassh., B. botryoides and B. boreoharlingii, are placed in the informally named Begonia tiliifolia group. A key, descriptions, illustrations and distribution maps are provided for the members of the Begonia tiliifolia group, and its sectional classification is discussed.